Hyperglycemia in stroke impairs polarization of monocytes/macrophages to a protective noninflammatory cell type - Khan, Mahtab A.; Schultz, Sina; Othman, Alaa; Fleming, Thomas; Lebrón-Galán, Rafael; Rades, Dirk; Clemente, Diego; Nawroth, Peter Paul; Schwaninger, Markus (The journal of neuroscience, 2016)
Hyperglycemia is common in patients with acute stroke, even in those without preexisting diabetes, and denotes a bad outcome. However, the mechanisms underlying the detrimental effects of hyperglycemia are largely unclear. In a mouse model of ischemic stroke, we found that hyperglycemia increased the infarct volume and decreased the number of protective noninflammatory monocytes/macrophages in the ischemic brain. Ablation of peripheral monocytes blocked the detrimental effect of hyperglycemia, suggesting that monocytes are required. In hyperglycemic mice, α-dicarbonyl glucose metabolites, the precursors for advanced glycation end products, were significantly elevated in plasma and ischemic brain tissue. The receptor of advanced glycation end products, AGER (previously known as RAGE), interfered with polarization of macrophages to a noninflammatory phenotype. When Ager was deleted, hyperglycemia did not aggravate ischemic brain damage any longer. Independently of AGER, methylglyoxal reduced the release of endothelial CSF-1 (M-CSF), which stimulates polarization of macrophages to a noninflammatory phenotype in the microenvironment of the ischemic brain. In summary, our study identified α-dicarbonyls and AGER as mediators by which hyperglycemia lowers the number of protective noninflammatory macrophages and consequently increases ischemic brain damage. Modulating the metabolism of α-dicarbonyls or blocking AGER may improve the treatment of stroke patients with hyperglycemia. - SIGNIFICANCE STATEMENT Although glucose is the main energy substrate of the brain, hyperglycemia aggravates ischemic brain damage in acute stroke. So far, clinical trials have indicated that insulin treatment provides no solution to this common clinical problem. This study shows, in an experimental stroke model, that hyperglycemia interferes with the polarization of monocytes/macrophages to a protective cell type. Key players are α-dicarbonyls and the receptor for advanced glycation end products (AGER). Deletion of AGER normalized monocyte/macrophage polarization and reversed the detrimental effects of hyperglycemia, suggesting new avenues to treat stroke patients.
Gesehen am 11.05.2020